Adding Flexible Instrumentation to a Curved Videolaryngoscope: A Novel Tool for Laryngeal Surgery. (25th June 2020) - Schild, Leon R.; Böhm, Felix; Boos, Marco; Kahrs, Lüder A.; Coburger, Jan; Greve, Jens; Dürselen, Lutz; Hoffmann, Thomas K.; Schuler, Patrick J.
Abstract : Objectives: Transoral surgery of the larynx with rigid instruments is not always possible. This may result in insufficient therapy or in an increased need for open surgery. For these patients, alternative surgical systems are needed. Here, we demonstrate a curved prototype for laryngeal surgery equipped with flexible instruments. Study Design: Pre‐clinical user study in an ex vivo porcine laryngeal model. Methods: The prototype was built from established medical devices, namely a hyperangulated videolaryngoscope and modified flexible instruments as well as three‐dimensional printed parts. Feasibility of laryngeal manipulation was evaluated in a user study (n = 19) with a porcine ex vivo laryngeal model. Using three different visualization technologies, the participants performed various fine motor skills tasks and rated the usability of the system on a 5‐point Likert scale. Results: Exposure, accessibility, and manipulation of important laryngeal structures were always possible using the new prototype. The participants needed considerably less time (mean, 96.4 seconds ± 6.4 seconds vs. 111.5 seconds ± 4.5 seconds, P = .18), reported significantly better general impression (mean score 3.0 vs. 3.8, P = .041 ) and significantly lower user head and neck strain (2.6 vs. 1.7, P = .022) using a 40‐inch television screen as compared to a standard videolaryngoscope monitor. Conclusion: The results indicate that our curved prototype and large monitor visualization may provide a cost‐effective minimally invasive alternative for difficult laryngeal exposure. Its special advantages include avoiding the need for a straight line of sight and a simple and cost‐effective construction. The system could be further improved through advances in camera chip technology and smaller instruments. Laryngoscope, 131:E561–E568, 2021